Meta-data and dive summary - Elliott, Kyle H.; Hare, James F.; Le Vaillant, Maryline; Gaston, Anthony J.; Ropert-Coudert, Yan; Anderson, W. Gary (Dryad Digital Repository, 2014)
This file has two tabs. The first tab provides the meta-data collected along with each deployment, such as sex and age of each bird. The second tab tabulates the depth and duration of all dives completed by chick-rearing birds within the dataset that were >5 m in depth. We assumed that the pressure sensor of all Lotek TDRs were comparable. However, as we deployed Little Leonardo and Lotek TDRs simultaneously, we were able to demonstrate that they agreed on dive duration but not dive depth. All Little Leonardo depth values in this spreadsheet have been converted to their equivalent Lotek depth using the equation given in the manuscript: Lotek Depth = 0.897*(Little Leonardo Depth) + 0.781 (R2 = 0.998). Care should be taken when comparing different devices because of differences in the calibration of the pressure transducer and because larger devices impact the dive behaviour of murres (Elliott et al. 2007. CJZ).